Response of Local rice cultivar to Zinc and Boron application (Baghdad Science Journal, 2011)
Five levels of Zn-EDTA fertilizer and foliar application of boron were used to study the local rice response through studying of some vegetative and reproductive growth characters, by conducting two field experiments at Kanipanka Agricultural Research Station during the summer season of 2004 by using RCBD with three replications. Significant differences were found in studied characters, there were increase in the number of days from seeding to 50% flowering (94.330-96.233) days, from 50% flowering to physiological maturity (37.50-38.28) days, plant height (82.50-91.423) cm and LAI (5.441-7.525). Reproductive characters such as number of grains panicle-1 (74.11-85.88), number of panicles m-2 (321.00-426.083), biological yield (8166.166-11082.600) kg ha-1 and yield which increased from 3101.333 to 3862.166 kg ha-1 as Zn level increased from fo to f5, but in exp. No 2 although final yield increased from 3100.333 to 3791.500 kg ha-1, but there was increasing in sterility% from 15 for fo to 27 for f5 with boron foliar application. Results of the study indicate to positive response of local rice cultivars to zinc application due to the lack in zinc availability in sulaimani region.